ANALYSIS OF CAFE MANAGEMENT STRATEGIES ON CUSTOMER INTEREST (CASE STUDY OF CAFE PANAMA) - Putri, Tri Reskita; Musa, Muh. Ichwan; Haeruddin, Muh. Ilham Wardhana; Hasbiah, Siti; Aswar, Nurul Fadilah (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the strategies carried out by Panama Coffee and Dining in Makassar City based on internal and external factors and using SWOT analysis as a reference. The research method used is descriptive qualitative, using interviews, direct observation and other related documents. The findings of this study explain that Panama Coffee and Dining currently faces threats from outside the company, but currently these threats can be suppressed and minimized by maximizing and optimizing the internal strengths possessed by Panama Coffee and Dining. Based on SWOT analysis, Panama Coffee and Dining is in quadrant II on the SWOT diagram. The strategy that must be applied is to use the company's strengths to take advantage of long-term opportunities by means of a diversification strategy. The diversification strategy in question is how Panama Coffee and Dining can increase development, sales and profits through the expansion of its market sector. This strategy will be the basis for Panama Coffee and Dining to increase customer interest, especially in Makassar City.